Doubly stratified non-Newtonian nanofluid flow featuring nonlinear convection - Shahzadi, Iqra; Kausar, Nabeela (International journal of numerical methods for heat & fluid flow, 2020)
Purpose The formulation of nonlinear convective non-Newtonian material is reported in this communication. Aspects of thermal radiation and heat source are taken into account for heat transport analysis. The novel stratifications (thermal and solutal) and convective conditions are considered simultaneously. The boundary-layer concept is implemented to simplify the complex mathematical expressions. Design/methodology/approach The well-known optimal homotopy scheme develops the computations. Optimal values regarding nonzero auxiliary variables are calculated and examined. Findings Nonlinear convective flow; Thixotropic non-Newtonian material; Thermal radiation; Heat source; Stratifications and convective conditions; Buongiorno model. Originality/value To the best of authors’ knowledge, no such analysis has yet been reported.